Immigration reduces selection in water microbial community assembly - Zhang, Fen-Guo; Wu, Kefan; Zhang, Sanqing; Liang, Furong; Du, Zhihua; Wang, Yongji; Zhang, Quan-Guo (Frontiers in Microbiology, 2025)
To investigate the influence of immigration on the selection in structuring local water bacterial communities, we conducted a new community assembly experiment using microcosms filled with sterile original water medium under outdoor conditions. We collected air particulate matter from dust pooled from samples collected at 10 locations across ~20 km in a warm temperate region in Linfen City (northern China). The immigration rates were increased by introducing air particulate matter into the microcosms. The diversity, structure, and composition of the bacterial community in the water were assessed using 16S rRNA gene amplicon sequencing on the 13th and 60th days after the start of the experiment. Our results showed that increasing immigration did not lead to significant changes in the overall diversity of the total bacterial community on the 13th day. However, on the 60th day, diversity significantly increased. The variation explained by the environment substantially decreased from the 13th to the 60th day. The amount decreased from the control to the high immigration treatments, with a range of 65.0 to 29.8% on the 13th day and 34.0 to 15.4% on the 60th day. The dominant phyla differed significantly. In the early stage, Proteobacteria (69.6%) accounted for a higher relative average abundance, while Firmicutes (4.6%), Cyanobacteria (6.0%), Planctomycetota (8.1%), Verrucomicrobiota (2.0%), and Halobacterota (0.9%) were more abundant in the late stage. Additionally, the late stage had an average of 33 phyla, compared to 15 phyla in the early stage. All the results suggested a minimal role of dispersal limitation in structuring water bacterial communities in the early stage, whereas, in the late stage, the bacterial communities might experience dispersal swamping in our study area. Variance partitioning indicated that throughout the experiment, increasing immigration weakened the signal of environmental selection in the water microbial community assembly. These results expand our understanding of the impact of immigration on environmental selection and provide insights into the varying importance of dispersal and selection on microbial community assembly at different stages of succession.